Haematopoietic Recovery On Induction Therapy In Acute Lymphoblastic Leukaemia By Automated Reticulocyte Analysis - Yesmin, MS; Nesa, A; Sultana, T; Roy, CK; Rahman, Md Quddusur; Ahmed, AN Nashimuddin (Bangladesh Journal of Pathology, 2011)
Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy in Bangladesh. ALL is treated with chemotherapy due to high responsiveness. After chemotherapy infection may occur which increases the time of aplasia. For this purpose, reliable laboratory tests that will indicate early haematological recovery are needed. At present, absolute neutrophil count (ANC), reticulocyte counts and peripheral blood film (PBF) examination are used after chemotherapy for prediction of bone marrow recovery. Reticulocyte quantification in the peripheral blood samples, as a percentage or absolute count with immature reticulocyte fraction (lRF) are a reliable measure of haematological recovery established by many studies. This cross sectional study was carried out to evaluate the haematopoietic recovery in children with ALL by automated reticulocyte analysis. Total fifty patients were enrolled in this study on remission induction phase. They received the drugs of the protocol of UKALL-XI. All patients were between 8 months to 15 years age range with a mean age of 5.5 ±3.2. In this study the recovery of reticulocyte percentage occurred at a median of 20 days; ARC 18 days; IRF 16 days; HFR 18 days and ANC was obtained after a median of 23 days. This study established that among the various parameters IRF recovered earlier than others. Keywords: Immature Reticulocyte Fraction(lRF); High fluorescent reticulocyte (HFR); Low fluorescent reticulocyte (LFR); Middle fluorescent reticulocyte (MFR); Absolute neutrophil count (ANC); Absolute Reticulocyte count(ARC). DOI: http://dx.doi.org/10.3329/bjpath.v26i1.9128 BJPATH 2011; 26(1): 10-13